THU0120 Is Early DMARD Use Associated with Less Joint Replacement Surgery? an Analysis of 5, 199 Incident Rheumatoid Arthritis (RA) Patients. (10th June 2014) - Moura, C.; Abrahamowicz, M.; Beauchamp, M.-E.; Lacaille, D.; Wang, Y.; Bombardier, C.; Widdifield, J.; Hanly, J.G.; Boire, G.; Feldman, D.; Maksymowych, W.; Peschken, C.; et al.
Abstract : Background: Early DMARD use in RA may prevent damage and possibly, need for joint replacement. Objectives: To assess joint replacements within incident RA patients in Quebec, Canada, and potential associations with early DMARD use. Methods: A cohort of incident RA patients was identified from Quebec's physician billing and hospitalization databases from 2002-2008; all patients covered by the provincial drug insurance for the duration of the study were included in analyses. We used Cox regression with time-dependent variables for: 1) methotrexate (MTX) use, 2) other non-biologic DMARDs and 3) anti-tumor necrosis factor (TNF) agents. Models were adjusted for baseline sociodemographic characteristics, co-morbidity including pre-existing osteoarthritis, and prior health service use, and for time-dependent variables reflecting cumulative use of other drugs (COXIBs, NSAIDs, and systemic steroids) and time-dependent indicators of disease severity (extra-articular RA features and number of rheumatology visits). The outcome (any joint replacement) was defined using procedure codes. Results: During follow-up, 321 joint replacements occurred among 5, 199 incident RA patients observed for a total of 19, 693 years (1.6 events/100 person-years). The best-fitting models relied on cumulative duration of MTX and cumulative duration of non-MTX traditional DMARD use in the first year after RA diagnosis. Controlling for anti-TNF exposure, joint replacement rates throughout follow-up appeared to be significantly lower with greater cumulative MTX and with greater cumulative non-MTX traditional DMARD use in the first year of RA (Hazard ratio, HR=0.95 per month of MTX use, 95% Confidence Interval, CI 0.91-0.98; HR=0.93 per month of use of non-MTX traditional DMARDs, 95% CI 0.90-0.97). However, patients receiving both MTX and non-MTX traditional DMARDs, concurrently or sequentially, within the first year after RA onset, had a significantly higher risk of joint replacement than those who used only one of the two drug classes within the first year. We could not establish independent effects for anti-TNF agents. Conclusions: Higher cumulative use of MTX and higher cumulative use of non-MTX traditional DMARDs within the first year after RA diagnosis appeared to be associated with fewer joint replacements. This may be consistent with joint-sparing effects of aggressive, early use of these drugs, though a causal link cannot be established with these observational data. The increased joint replacement risk in patients taking both MTX and other DMARDS, concurrently or sequentially, in the first year, suggests potential confounding by indication, as patients taking multiple drugs may have more severe disease, and greater risk for joint damage. References: Gramling A, O'Dell JR (2012). Initial management of rheumatoid arthritis. Rheum. Dis. Clin. North Am. 38 (2): 311–25. Acknowledgements: Canadian Institutes for Health Research/Drug Safety and Effectiveness Network (CIHR/DSEN) Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.3061